RESPONSE TOWARDS CLIMATE CHANGE: A COMPARATIVE STUDY OF SELECT CHAIN OF HOTELS IN NORTH INDIA - Ramjit, Dr.; Mir, Mudasir Ahmad (Revista de turism - studii și cercetări în turism, 2020)
The study endeavours the perception of hotel’s managers towards Climate Change. The response was sought from 119 senior and mid-level managers of the different departments of the two chain of hotels namely Taj group and Radisson group located in the northern part of the country (Srinagar, Jammu, Amritsar, Jalandhar and Chandigarh and New Delhi). Descriptive statistics & Independent t -test were applied to analyse the response of select hotels towards various climatic factors like “Perception of Climate Change Impacts on Hotel’s Location; Level of Implementation of UNWTO and UNEP (2008). The findings of the study revealed that Hotel chains (Radisson and Taj) perception with regard to temperature changes is higher in summer as compared to winter temperature and also disclosed that hotel sector has an obligation to react to environmental change and will attempt to react to environmental change regardless of fact whether the administration would support it or not. With regard to the level of implementation measures as suggested by the UNWTO and UNEP for accommodation sector, there are certain measures where the selected hotels have shown low level of implementation. Key Words: Climate Change, Hotel’s manager’s perception, hospitality industry